Personal experiences and climate change - Gunnäs,Petter (2021)
When the consequences of climate change now are starting to be seen more frequent in the industrialised world it raises an important question on what impact these natural hazards might have on individual concern for climate change. Using the case of the 2014 wildfires that took place in Västmanlands Län I explore whether or not living in the same region as this natural hazard impacts concern for climate change by individuals experiencing a decrease in psychological distance to the matter. With the cumulative dataset from SOM institute that have for the last two decades included a question on concern for climate change in their national serves I will test my hypothesis by using non-linear differences in differences (DiD). With this method comparing Västmanlands Län to a contrafactual constructed by a group of similar regions in Sweden I found that the wildfires had no significant effect on concern for climate change for the individuals living in the same region as the fire. In the DiD logistic regression the P-value of the DiD interaction coeffect is 0.510. When using a linear probability model to get heteroscedastic and autocorrelated consistent standard errors the p-value only decreases to 0.183. Thus the conclusion is that in the medium to long run the wildfire did not impact people living in Västmanlands Län concern for climate change.
Keywords: Personal experiences; concern climate change; differences in differences